FORESTRY FOR SUSTAINABLE MANAGEMENT - Menon, A. R. R. (Journal of Dharma, 2014)
Sustainable management of natural resources has become a key issue for survival of life. The most appropriate method to do that would be to assess the ecological sustainability by way of understanding the ecosystems/ landscape complexities and their uniqueness. Traditionally monitoring of populations or habitats involved field based observations, an approach that is time consuming and also requires specialist’s involvement. Remote sensing and GIS technology can be used as an effective tool in resource assessment.